Time-resolved studies define the nature of toxic IAPP intermediates, providing insight for anti-amyloidosis therapeutics - Andisheh Abedini; Annette Plesner; Ping Cao; Zachary Ridgway; Jinghua Zhang; Ling-Hsien Tu; Chris T Middleton; Brian Chao; Daniel J Sartori; Fanling Meng; Hui Wang; Amy G Wong; et al. (eLife, 2016)
Islet amyloidosis by IAPP contributes to pancreatic β-cell death in diabetes, but the nature of toxic IAPP species remains elusive. Using concurrent time-resolved biophysical and biological measurements, we define the toxic species produced during IAPP amyloid formation and link their properties to induction of rat INS-1 β-cell and murine islet toxicity. These globally flexible, low order oligomers upregulate pro-inflammatory markers and induce reactive oxygen species. They do not bind 1-anilnonaphthalene-8-sulphonic acid and lack extensive β-sheet structure. Aromatic interactions modulate, but are not required for toxicity. Not all IAPP oligomers are toxic; toxicity depends on their partially structured conformational states. Some anti-amyloid agents paradoxically prolong cytotoxicity by prolonging the lifetime of the toxic species. The data highlight the distinguishing properties of toxic IAPP oligomers and the common features that they share with toxic species reported for other amyloidogenic polypeptides, providing information for rational drug design to treat IAPP induced β-cell death.